Exploring the Lived Experience of Congestive Heart Failure Patients in Bulukumba Regency, Indonesia - Andi Baso Tombong; Irfanita Nurhidayah; Andi Nurlaela Amin (Comprehensive Health Care, 2022)
Congestive Heart Failure has become a major problem in the society worldwide with high prevalence, high mortality and morbidity, resulting in huge financing for care, carrying such a large burden on patients. In Indonesia, congestive heart failure has become one of the main killers. The prevalence of heart disease in Indonesia from year to year is increasing. Patients with CHF generally have various health problems, functional physical limitations, as well as behavioural and psychological symptoms that affect daily life and a long-term prognosis. The impact of heart failure on patients provides its own experience for sufferers. Therefore, CHF sufferers need sufficient coping to deal with the condition. This can certainly be obtained from a good support system as well, including family support as a care provider at home. To date, research that explores coping and family support specifically for people with heart failure and in-depth exploration of the experiences of people with CHF, especially in Bulukumba regency, has been limited. This study aims at exploring the experience of CHF patients in living their daily lives. This study used a qualitative approach with phenomenology design. The study had been conducted throughout September – October 2018. Using purposive sampling technique, three outpatient individuals with CHF was interviewed and the data was analysed by employing thematic analysis. The findings highlight three themes, including feeling after diagnosed with CHF, coping mechanism, and the importance of family support. This study suggest that approach towards providing health services to individuals with CHF should incorporate patient’s experience-based interventions to support their therapy adherence and to improve their quality of life.